Variables Affecting the Yield of Oil from Tobacco Seed - Parlak, Adnan; Karabas, Hulya; Ozsert, Ibrahim (Asian Journal of Chemistry, 2010)
In this study, a parametric study was implemented for the purpose of optimization of the efficient oil extraction for a continuous oil production plant. The parameters affecting oil extraction from the tobacco seed oil in the study were chosen as temperatures and seeds-to-solvent ratio, grinding size (mm) of tobacco seed, stirring rate and duration. Mass based seeds-to-solvent ratio, stirring rate and grinded seed size were found to be effective on oil extraction. It was reached maximum oil extraction in the conditions of 40 ºC, 600 rpm stirring rate, 0.4 mm grinding size and 1 to 3 seeds-to-solvent ratio. The amount of oil was extracted from the tobacco seed oil was measured as 45 %. This is the highest amount of extracted oil from the tobacco seed oil up to day in the open literature.